Citrulline metabolism in cultured fibroblasts : citrullinemia analysis and nitric oxide production - Shires, Karen Lesley (Division of Chemical Pathology, 2018)
A citrullinemic fibroblast cell line was used in this study to investigate two biochemical pathways involving citrulline. In the first section, the genetic mutation responsible for the argininosuccinate synthetase (-ASS) deficiency (1-5% activity) in this cell line was investigated. PCR analysis of the ASS cDNA revealed that the mRNA coding region (1236bp) was intact, showing no signs of major rearrangements. The ASS cDNA (1307bp) was cloned and sequenced and showed the presence of a single base mutation at position 1045bp, which represented a G->A transition. This mutation resulted in a glycine -> serine amino acid substitution at position 324 in the ASS subunit protein sequence. Although this glycine residue was not found to occur in any potential substrate binding sites, it was shown to be highly conserved among species, indicating a possible role of this amino acid in ASS catalytic activity. In the second section, the presence of the nitric oxide pathway in fibroblasts was investigated. Inducible nitric oxide synthase activity was assayed by measuring the production of ¹⁴C-citrulline from ¹⁴C-arginine after cytokine stimulation. By using the citrullinemic cell line (ASS deficient) any citrulline that may be produced by this pathway would accumulate, allowing detection. Under the assay conditions that were tested, no detectable ¹⁴C-citrulline was formed. Evidence suggests that human fibroblasts have the potential to synthesise nitric oxide, although a more sensitive assay system may need to be employed (longer cytokine activation, nitrite/nitrate detection).